ANALISIS KANDUNGAN LOGAM TIMBAL, KADMIUM DAN MERKURI DALAM PRODUK JAMU PEGAL LINU YANG BEREDAR DI KOTA PEKANBARU - Okta Letri Husna; Tengku Abu Hanifah; Ganis Fia Kartika (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Jamu is one of traditional medicine that is still consumed today. The content of heavy metals (Pb, Cd and Hg) in jamu product is very dangerous to humans, because it can cause health problems such as liver and kidney excreation. The aim of this research was to analyzed the content of lead, cadmium and mercury in the jamu pegal linu product. Six sample products of jamu pegal linu were purchased randomly in traditional Pekanbaru markets to be analyzed by atomic absorption spectrophotometer and cold-vapor atomic absorption spectrophotometer with wet digestion process. The result showed that the content of Pb and Hg in the samples were exceeded the limit of BPOM RI, whereas Cd metal was found below the limit that allowed by BPOM RI.